The interpretation and application of principles of corporate governance in the South African Airways - Ntene, Ntswinyane Semi (My University, 2020)
Corporate Governance refers to the manner in which companies are directed and controlled. It is concerned with striking a balance between economic and social goals and between individuals and communal goals. The South African Airways (SAA) has recently become one of the worst underperformers amongst the existing State-Owned Companies (SOCs). It has become evident that there was an extensive meddling in SAA’s day to day operations by its chairlady, who has been placing orders and making contractual commitments on the SAA’s behalf, as well as involving herself in managerial decisions in quite inappropriate ways. The Chief Executive Officers (CEOs) of the SAA were changed within a period of four years. It had at some stage developed eight strategies within six years but implemented none of those strategies. The SAA also experienced board infightings which led to the firing of the entire board by the shareholders. The cause of these challenges, as argued in this paper, is poor interpretation and application of corporate governance principles in the SAA. This paper is intended to interpret the principles regulating corporate governance and the application thereof within the context of the SAA. In addition, the paper discusses the comparative analysis with reference to the corporate governance of South Africa and the United Kingdom (UK).
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2020
Keywords: Corporate governance; State-owned companies; Corporations; South African Airways; Corporate governance -- South Africa; Government business enterprises; Directors of corporations